ANALISIS GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA PT. TIRTA INVESTAMA PANDAAN - jurnalpps pps; Ekkar Wityanto Heru Subrata; C. Sri Hartati; Ruddy Wiroko (Jurnal Manajerial Bisnis, 2019)
This study aims to analyze transformational leadership style, organizational culture on employee performance with work motivation which is moderated by PT Tirta Investama Pandaan. The population in this study were employees who worked in Manufacturing Area 2 of PT Tirta Ivestama Pandaan. The number of samples taken by 58 respondents with the sampling method was simple random sampling. The analysis tool used is multiple linear regression with SPSS and hypothesis testing. The results showed that transformational leadership style was not significant to employee performance, organizational culture was not significant to employee performance, transformational leadership style had a significant effect on employee work motivation, organizational culture significantly influenced work motivation; Transformational leadership style and organizational culture increase motivation towards performance, transformational leadership style and organizational culture improve performance with work motivation as a moderating variable. Keywords: transformational leadership style, organizational culture, job motivation, employee performance.